2013
DOI: 10.1002/icd.1810
|View full text |Cite
|
Sign up to set email alerts
|

Children's Understanding of Second‐Order False Belief: Comparisons of Content and Method of Assessment

Abstract: This research examined children's performance on second‐order false belief tasks as a function of the content area for the belief and the method of assessing understanding. A total of 70 kindergarten and first‐grade children responded to four second‐order stories. On two stories, the task was to judge a belief about a belief, and on two, the task was to judge a belief about an emotion. On one trial within each group, the task was to predict the target's belief, and on one trial, the task was to explain the bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 34 publications
2
36
0
1
Order By: Relevance
“…Once children have reached a certain threshold of mental state understanding and they spend more time with peers in middle childhood, connections between siblings and ToM may disappear. Indeed, two recently published studies document null relations between siblings and ToM in 6-to 10-year-olds, as measured through first-and second-order false-belief tasks (Calero, Salles, Semelman, & Sigman, 2013;Miller, 2013). The question is far from resolved, however, and may depend upon sample size as well as the specific ToM measures used.…”
Section: Siblingsmentioning
confidence: 93%
See 1 more Smart Citation
“…Once children have reached a certain threshold of mental state understanding and they spend more time with peers in middle childhood, connections between siblings and ToM may disappear. Indeed, two recently published studies document null relations between siblings and ToM in 6-to 10-year-olds, as measured through first-and second-order false-belief tasks (Calero, Salles, Semelman, & Sigman, 2013;Miller, 2013). The question is far from resolved, however, and may depend upon sample size as well as the specific ToM measures used.…”
Section: Siblingsmentioning
confidence: 93%
“…Here, we describe four additional tasks researchers utilize to test psychological understanding in older children and adults: (1) Second-Order False Belief, (2) Reading the Mind in the Eyes, (3) Strange Stories, and (4) Faux Pas. While first-order ToM tasks test children's knowledge about another person's beliefs or feelings, second-order ToM measures test participants' understanding about a person's thoughts regarding how another person thinks or feels, typically involving misconceptions or deception (Miller, 2009(Miller, , 2013Perner & Wimmer, 1985). Third-order ToM tasks go a step further-testing knowledge about another person's belief (Liddle & Nettle, 2006).…”
Section: Further Tests Of Advanced Theory Of Mind In Middle Childhoodmentioning
confidence: 98%
“…Sibling composition provides an interesting test case because several studies have shown that 3-to 6-year-olds with more siblings, especially older siblings, demonstrate superior ToM performance compared with children with fewer or no siblings (e.g., Farhadian, Gazanizad, & Shakerian, 2011;Lewis, Freeman, Kyriakidou, Maridaki-Kassotaki, & Berridge, 1996;McCalister & Peterson, 2006, 2007, 2013Perner et al, 1994;Ruffman, Perner, Naito, Parkin, & Clements, 1998;Wolfe, Want, & Siegal, 2003; but see Carlson & Moses, 2001;Cole & Mitchell, 2000;Cutting &Dunn, 1999, andHughes &Ensor, 2005, for examples of null effects). Researchers have interpreted these data to indicate that siblings provide social opportunities that improve young children's knowledge about mental states, with older siblings being particularly advantageous because they serve as social mentors to the younger ''apprentices'' (Hughes et al, 2014;Perner et al, 1994;Ruffman et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, more advanced, or higher order, social understanding includes the ability to coordinate relations among multiple mental states across multiple individuals. For instance, children's reasoning about recursive mental beliefs, such as John's belief about what Mary believes, generally improves around 5-to 6-years of age (Miller, 2012(Miller, , 2013. As understanding of mental states advances, children are able to comprehend increasingly complex and subtle social events.…”
Section: Introductionmentioning
confidence: 99%
“…Most 7-to 9-year-olds, as well as some 6-year-olds, correctly recognized John's false belief about Mary's belief concerning the truck's location. However, with simplified stories with fewer words, characters, and scenes, subsequent studies have found that children as young as five years of age can successfully identify higher-order false beliefs (e.g., Coull, Leekam, & Bennett, 2006;Hayashi, 2007;Miller, 2013;Sullivan, Zaitchik, & Tager-Flusberg, 1994). Thus, by age five years, children may have some ability to engage in higher-order belief reasoning, but this ability continues to improve, and children do not achieve ceiling performance on the more challenging tasks until 7-or 8-years of age.…”
Section: Introductionmentioning
confidence: 99%